Photon-stimulated recombination of self-trapped holes with electrons in pre-irradiated solid Ar - Gumenchuk, G.B.; Bludov, M.A.; Belov, A.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Spatially separated stable charge centers – trapped electrons and self-trapped holes – are generatedin Ar cryocrystals by a low-energy electron beam. A combination of the cathodoluminescence and photon-stimulated luminescence methods has been used to probe recombination reactions. Photon-stimulated vacuum ultraviolet intrinsic recombination luminescence from pre-irradiatedsolid Ar was detected for the first time. The 1.96 eV laser light has been demonstrated to releaseelectrons from their traps that gives rise to the well-known M-band at 9.8 eV. Additional information on the photostability of charge centers at low temperatures has been obtained.